Characterization of gut microbiota in patients with primary hepatocellular carcinoma received immune checkpoint inhibitors: A Chinese population-based study. Issue 37 (11th September 2020) - LI, Lili; Ye, Jiajian
Abstract : Abstract: Hepatocellular carcinoma (HCC) is one of the most common neoplasms encountered, and its incidence is increasing worldwide. In this study, we explored the characteristics of gut microbiota in patients with primary hepatocellular carcinoma in advanced stage who received immune checkpoint inhibitors (ICIs) based on a large population with hepatitis B virus infection. An initial cohort of 65 patients with metastatic melanoma were included in this study. All patients were treated with ICIs at Fujian provincial geriatric hospital between August 2016 and June 2018. The 16S rDNA V4 region was amplified by Polymerase chain reaction and sequenced on the MiSeq platform. We found that the diversities of the gut microbiota in HCC who received ICIs were obviously increased. Negative feedback, which is controlled by interplay between microbial metabolic activities and host pathways, is thought to promote high bacterial diversity. We focused on the Faecalibacterium genus in response group, and Bacteroidales order in non-response group, and stratified patients into high versus low categories based on the median relative abundance of these taxa in the gut microbiome. Patients with high Faecalibacterium abundance had a significantly prolonged PFS versus those with a low abundance. Conversely, patients with a high abundance of Bacteroidales had a shortened progressive free survival compared to those with a low abundance. In summary, the present study examined the oral and gut microbiome of HCC patients undergoing immune checkpoint inhibitors immunotherapy. Significant differences were observed in the diversity and composition of the patient gut microbiome of responders versus non-responders.